RTID-01. ONC108: A RANDOMIZED PHASE 3 STUDY OF ONC201 IN PATIENTS WITH NEWLY DIAGNOSED H3 K27M-MUTANT DIFFUSE GLIOMA. (14th November 2022) - Arrillaga-Romany, Isabel; Lassman, Andrew; McGovern, Susan; Mueller, Sabine; Nabors, L Burt; van den Bent, Martin; Vogelbaum, Michael; Allen, Joshua E; Melemed, Allen; Tarapore, Rohinton; Yang, Dewen; Wen, Patrick Y; et al.
Abstract: BACKGROUND: H3 K27M-mutant diffuse midline glioma is a universally fatal malignancy primarily affecting children and young adults; while radiotherapy (RT) provides transient benefit, no effective systemic therapy is currently available. ONC201, a first-in-class imipridone, is an oral, blood-brain barrier penetrating, selective small molecule antagonist of dopamine receptor D2/3 (DRD2) and agonist of the mitochondrial protease ClpP. An integrated pooled analysis of objective response in ONC201-treated patients enrolled in one of five open-label trials has previously demonstrated efficacy in patients with recurrent disease. This phase 3 trial will be the first randomized, controlled study evaluating ONC201 in patients with H3 K27M-mutant disease. METHODS: ONC108 is a randomized, double-blind, placebo-controlled, parallel-group, international Phase 3 study of ONC201 in patients with newly diagnosed H3 K27M-mutant diffuse glioma. Patients will be randomized to receive once-weekly ONC201 or placebo following standard frontline radiotherapy. Primary efficacy endpoints are overall survival (OS) and progression-free survival (PFS) in all participants; PFS will be assessed with the response assessment in neuro-oncology-high grade glioma by blind independent central review. Other objectives include assessments of safety, additional efficacy endpoints, clinical benefit, quality of life, pharmacokinetics, biomarkers, and healthcare resource utilization. Eligible patients will have histologically confirmed H3 K27M-mutant diffuse glioma, a Karnofsky/Lanksy performance status ≥ 70, and completed first-line radiotherapy. Eligibility will not be restricted based on age; however, patients must be ≥ 10 kg at time of randomization. Patients with a primary spinal tumor, diffuse intrinsic pontine glioma, leptomeningeal disease, or cerebrospinal fluid dissemination are not eligible.